Fenomenologi Self Declare Sertifikasi Halal Bagi Pelaku UMKM Produk Makanan dan Minuman Untuk Peningkatan Awareness Sertifikasi Halal Di Kabupaten Pasuruan - Aslikhah; Moh. Mukhsinin Syu’aibi (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The purpose of this study 1) to determine the phenomenon of self-declaring halal certification for food and beverage product MSME actors in Pasuruan 2) to understand the knowledge of the self-declaring halal certification concept for food and beverage product MSME actors in Pasuruan 3) to prove self-declaring for MSME’s halal certification, food and beverage products can increase awareness of halal certification in Pasuruan . This research is a qualitative research with a phenomenological approach to describe and understand the essence of the experience of MSME in food and beverage products conducting halal certification through the self-declaring route in Pasuruan Regency. The results of this study indicate that there are 3 typologies in the self-declaring phenomenon of halal certification for food and beverage product MSME actors in Pasuruan Regency, namely 1) food and beverage product MSME actors who state that they understand self-declaring halal certification, 2) food and beverage product MSME actors typology. and beverages stating that they do not understand self-declaring halal certification and 3) typology of food and beverage product MSME actors who state that they do not understand self-declaring halal certification with various arguments based on the level of understanding and experience felt by each food and beverage product MSME actor. drinks in Pasuruan Regency. It can be concluded that a good understanding, experience in applying for halal certification and intense assistance from halal product companions will increase awareness of halal certification through the self-declaring pathway for food and beverage product MSME actors in Pasuruan Regency.